A political ecology of speculative urbanism: The role of financial and environmental speculation in Jakarta's water crisis. (March 2023) - Colven, Emma
Jakarta, Indonesia's capital, is increasingly characterized by luxury real estate developments and high-profile infrastructural projects made possible by economic liberalization and finance capital. Yet these developments have contributed to Jakarta's struggles with chronic flooding, land subsidence, and water shortages. This paper contributes an empirical study of the spatial-temporal dynamics of speculative urbanism and the associated impacts on water resources and flood events in Jakarta. I use an urban political ecology approach to analyze mainland and offshore development. First, I show how financial speculation generates flood risk and the overexploitation of water resources, producing uneven socio-spatial distributions of risk. These transformations in Jakarta's hydroscape in turn threaten to undermine the city's viability as a site for speculative investment. I thus show how speculative urbanism can be threatened or disrupted by nonhuman agencies. Second, I illustrate a second form of speculation, which I refer to as environmental speculation. As Jakarta's water crisis has cast doubt on the future of the city itself as a place of habitation, the state explored an ambitious and potentially lucrative coastal defense project, while private developers have engaged in land reclamation. The turn toward offshore development illustrates how environmental speculation creates new opportunities for capital accumulation. I advance two arguments: first, in order to capture the full costs of speculative urbanism, it is imperative that urban scholars attend to its ecological dimensions. Second, an urban political ecology approach advances our understandings of speculative urbanism by illuminating its contradictions and limits.